Unlocking the nexus between leaf-level water use efficiency and root traits together with gas exchange measurements in rice (Oryza sativa L.) - Gobu, Ramasamy; Dash, Goutam Kumar; Lal, Jai Prakash; Swain, Padmini; Mahender, Anumalla; Anandan, Annamalai; Ali, Jauhar (MDPI, 2022)
Drought stress severely affects plant growth and development, causing significant yield loss in rice. This study demonstrates the relevance of water use efficiency with deeper rooting along with other root traits and gas exchange parameters. Forty-nine rice genotypes were evaluated in the basket method to examine leaf-level water use efficiency (WUEi) variation and its relation to root traits. Significant variation in WUEi was observed (from 2.29 to 7.39 µmol CO2 mmol−1 H2O) under drought stress. Regression analysis revealed that high WUEi was associated with higher biomass accumulation, low transpiration rate, and deep rooting ratio. The ratio of deep rooting was also associated with low internal CO2 concentration. The association of deep rooting with lower root number and root dry weight suggests that an ideal drought-tolerant genotype with higher water use efficiency should have deeper rooting (>30% RDR) with moderate root number and root dry weight to be sustained under drought for a longer period. The study also revealed that, under drought stress conditions, landraces are more water-use efficient with superior root traits than improved genotypes.